2006
DOI: 10.1159/000092471
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Findings in a Case with the Autosomal Recessive Type of Robinow Syndrome

Abstract: Objective: Our aim was to present a prenatally diagnosed case with Robinow syndrome in a consanguineous couple and discuss possible differential diagnosis in view of the literature. Methods: A 28-year-old pregnant woman gravida 2 para 1 was referred to the obstetric clinic of Kahramanmaras Sutcu Imam University presenting with a fetus having shortened upper and lower limbs at 33 weeks of gestation. Her medical history was unremarkable except for consanguinity. Prenatal ultrasonographic examination revealed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…By focusing on the characteristic phenotypical features in Robinow syndrome, among these especially the short disproportionate stature, the facial dysmorphology, and genital hypoplasia, we hypothesize that it is possible to detect and diagnose both the autosomal recessive and dominant forms prenatally. To the best of our knowledge, only two previous cases of prenatally diagnosed autosomal recessive Robinow syndrome (Percin et al 2001 and Guven et al 2006 ) and two cases of prenatally diagnosed autosomal dominant Robinow syndrome (Loverro et al 1990 and Castro et al 2013 ) have been reported in the literature.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…By focusing on the characteristic phenotypical features in Robinow syndrome, among these especially the short disproportionate stature, the facial dysmorphology, and genital hypoplasia, we hypothesize that it is possible to detect and diagnose both the autosomal recessive and dominant forms prenatally. To the best of our knowledge, only two previous cases of prenatally diagnosed autosomal recessive Robinow syndrome (Percin et al 2001 and Guven et al 2006 ) and two cases of prenatally diagnosed autosomal dominant Robinow syndrome (Loverro et al 1990 and Castro et al 2013 ) have been reported in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the thorax was observed to be narrower in comparison with the abdomen. In the recessive cases, Percin et al found shortening of the humerus and femur, and Guven et al found decreased femur and humerus lengths and shortening of the long bones of the forearms. Only in the dominant case of Castro et al , the facial dysmorphology was recognized prenatally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal diagnosis is possible from the 19th week of pregnancy by fetal ultrasonography. Assessment of the length of the long bones and the ulna/humerus ratio has been used in prenatal diagnosis 111…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the length of the long bones and the ulna/humerus ratio has been used in prenatal diagnosis. (9) This syndrome has to be differentiated from other causes of vertebral malsegmentation, rib hypoplasia, and forearm dysplasias like Aarskog-Scott syndrome, Opitz G syndrome and autosomal recessive spondylocostal dysostosis. These syndromes are differentiated by the characteristic facial changes and the genital hypoplasia of Robinow syndrome.…”
Section: Case Reportmentioning
confidence: 99%